Vegetative Propagation for Restoration and Conservation of Mangroves - Sithranga Boopathy, N.; Ramasubramanian, R. (Indian Forester, 2023)
Indian mangroves are biologically diverse with 46 true mangrove species belonging to 14 families and 22 genera found in 9 states and 4 Union Territories. Although the country is the third biggest in the global mangroves, it faces a serious problem of degradation mainly due to human activities such as agriculture, aquaculture and over-exploitation of resources. It is estimated that about 40% of the mangroves have been degraded in India, and hence, it is a matter of necessity to rehabilitate them with fast colonizing planting materials. These can be propagated vegetatively through using the techniques of cuttings, air-layering and grafting. However, still these techniques are not widely used for mangrove propagation and hence, the present work emphasized the merits of vegetative propagation in mangrove conservation.